Comparison of X-ray and neutron tomographic imaging to qualify manufacturing of a fusion divertor tungsten monoblock - Llion Evans (Fusion Engineering and Design, 2018)
Within a tokamak fusion energy device, the performance and lifespan of a divertor monoblock under high heat flux cycles is of particular interest. Key to this is the quality of manufacture, especially the material joining interfaces. Presented here is a comparative study between X-ray and neutron tomography to investigate the quality of manufactured monoblocks. Tungsten is a high attenuator of X-rays, thus X-ray tomography was performed on ‘region of interest’ samples where the majority of the tungsten armour was removed to reduce the attenuation path. Neutron tomography was performed on the full monoblock samples for non-destructive testing and on the ‘region of interest’ samples for direct comparison. Both techniques were shown to be capable of imaging the samples but having their own advantages and disadvantages relating to image accuracy and logistical feasibility. The techniques discussed are beneficial for either the research and development cycle of fusion component design or in quality assurance of manufacturing.